Kriminalitas Bukan Hal Tabu di Lampung - Abisyfa, Muhammad Fahrudin; Yusuf, Hudi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
this article reviews the problem of high crime rates in Lampung Province and how society and other aspects respond to / overcome this. Broadly speaking, things like crime itself are already attached to the island of SUMATRA, especially Lampung, whether it has become a habit or something that is a baton, but this is very bad and must be eliminated. Then what about law enforcement from the police that you must have thought about from the start, it is not strange if this question arises because there are several factors that make the police movement less than optimal to reduce the crime rate itself. Like the many crimes that occur and make the police as those responsible for this unable to carry out their own handling. Then there are several other factors including the lack of public trust in the performance of the police which according to them